“Akulah, Ibu Sang Raja!”: Posttraumatic Growth Penyintas Berdaya - Hauw, Andreas (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2024)
AbstractThe argument of this paper is that Bathsheba, in the stories of 2 Samuel 11-12 and 1 Kings 1:1-2:25, when read in narrative criticism emerge as an empowered survivor of sexual violence. The prophet Nathan, who became Bathsheba’s confidant, contributed to Bathsheba regaining her honor that was lost due to David’s rape. From a trauma studies perspective, Bathsheba experienced posttraumatic growth (PTG), which is the ability to overcome post-traumatic syndrome disorder (PTSD). This paper is useful in illustrating the narrative’s strategic tactics to get out of a helpless situation. The courageous attitude in expressing bitter experiences, good relationships with the environment, appreciation of life, the opening of new opportunities, and connection with God are factors of Bathsheba’s PTG. AbstrakArgumentasi tulisan ini adalah Batsyeba dalam kisah 2 Samuel 11-12 dan 1 Raja-raja 1:1-2:25, yang dibaca dalam kritik narasi (narrative criticism), akan tampil sebagai penyintas kekerasan seksual yang berdaya. NabiNatan, yang menjadi lingkungan terdekat Batsyeba, berkontribusi bagi Batsyeba untuk mendapatkan kembali kehormatan yang pernah hilang darinya karena rudapaksa Daud. Dalam kacamata studi trauma, Batsyeba mengalami posttraumatic growth (PTG), yaitu kemampuan mengatasi posttraumatic syndrome disorder (PTSD). Tulisan ini bermanfaat dalam menggambarkan taktik strategis narasi untuk keluar dari situasi tak berdaya. Sikap berani dalam mengungkapkan pengalaman pahit, relasi baik dengan lingkungan, penghargaan terhadap hidup, terbukanya kesempatan baru dan hubungan dengan Allah menjadi faktor PTG Batsyeba.